Rendahnya Rasa Hormat Siswa SD Inpres Makalonsouw Kepada Guru - Monica Valery Muntuan (Peneliti.net, 2023)
The formation of a moral nation cannot be separated from respect for elders. In order to manifest an attitude of respect for older people, parents should have instilled an attitude of respect since childhood. An attitude of respect is very important for life in order to become a better person for the homeland and the nation. This study aims to describe the low respect students have for teachers at SD Inpres Makalonsouw. The subjects of this study were students of SD Inpres Makalonsouw, school principals, teachers and parents. The research method used is descriptive qualitative research with a phenomenological approach. In data collection techniques by way of observation, interviews, and documentation studies. As for checking the validity using the persistence of observation and triangulation. The results of research on students' respect for SD Inpres Makalonsouw teachers. Based on the indicators determined by the researcher: (1) honorifics, (2) appreciation, (3) respect, (4) friendliness, (5) harmony, (6) politeness, (7) attitude/manners, and (8) speak language. The results of observations of SD Inpres Makalonsouw students and supported by interviews with teachers, the highest indicator of respect is respect followed by appreciation, politeness, harmony, friendliness, attitude/etiquette, language speech, honorifics. Based on the results of the discussion, the presence of a new teacher did not affect the respect of the students of SD Inpres Makalonsouw